Genetic Distances of Three Mollusk Species Investigated by PCR Analysis - Oh, Hyun (Dev Reprod, 2014)
Three species of Nortamea concinua (NC) and Haliotis discus hannai (HDH) from Tongyeong and Sulculus diversicolor supertexta (SDS) are widely distributed on the coast of the Yellow Sea, southern sea and Jeju Island in the Korean Peninsula under the innate ecosystem. There is a need to understand the genetic traits and composition of three mollusk species in order to evaluate exactly the patent genetic effect. PCR analysis was performed on DNA samples extracted from a total of 21 individuals using seven decamer oligonucleotides primers. Seven primers were shown to generate the unique shared loci to each species and shared loci by the three species which could be clearly scored. A hierarchical clustering tree was constructed using similarity matrices to generate a dendrogram, which was facilitated by the Systat version 10. 236 specific loci, with an average of 56.3 per primer, were identified in the NC species. 142 specific loci, with an average of 44.7 per primer, were identified in the HDH species. Especially, 126 numbers of shared loci by the three species, with an average of 18 per primer, were observed among the three species. Especially, the decamer primer BION-75 generated 7 unique loci to each species, which were identifying each species, in 700 bp NC species. Interestingly, the primer BION-50detected 42 shared loci by the three species, major and/or minor fragments of sizes 100 bp and 150 bp, respectively, which were identical in all samples. As regards average bandsharing value (BS) results, individuals from HDH species (0.772) exhibited higher bandsharing values than did individuals from NC species (0.655). In this study, the dendrogram obtained by the seven decamer primers indicates three genetic clusters: cluster 1 (CONCINNA 01~CONCINNA 07), cluster 2 (HANNAI 08~HANNAI 14), cluster 3 (SUPERTEXTA 15~SUPERTEXTA 21). Comparatively, individuals of HDH species were fairly closely related to that of SDS species, as shown in the hierarchical dendrogram of genetic distances.